Urban Nature as a Learning Context: Impacts on Literacy, and Intrinsic Motivation in Primary School Students - Dery Purnama Saefudin; Mulyadi; Restoeningroem; Gundah Noor Cahyo (English Language Education Department, Universitas Majalengka, 2025)
Literacy skills are a fundamental foundation in the academic development of elementary school students. However, conventional teaching methods often fail to engage students and foster their motivation to learn. This study aims to evaluate the effectiveness of learning through urban park exploration in improving students' literacy skills and intrinsic motivation. The research used a quantitative approach with a one-group pretest-posttest design, involving 50 third-grade students at Sekolah Alam Indonesia Cipedak. Data were collected through literacy tests and motivation questionnaires, and analyzed using descriptive statistics and a paired sample t-test. The results showed an increase in literacy scores from an average of 46.10 to 53.32, with a t-test result of t = -7.178, p = 0.000 (p < 0.05). Students’ intrinsic motivation was also high, with an average score of 4.04 (SD = 0.402). These findings suggest that real-world environmental exploration can enhance literacy while also fostering students’ internal drive to learn. This model supports Vygotsky’s sociocultural theory of learning and offers an alternative that is contextual, active, and enjoyable for elementary school students.